2015
DOI: 10.1016/j.cam.2014.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Levenberg–Marquardt method for solving systems of absolute value equations

Abstract: In this paper, we suggest and analyze the Levenberg-Marquardt method for solving system of absolute value equationsx R ∈ is unknown. We present different line search methods to convey the main idea and the significant modifications. We discuss the convergence of the proposed method.We consider numerical examples to illustrate the implementation and efficiency of the method. Results are very encouraging and may stimulate further research in this direction. MSC: 65K10, 65H10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…For instance, linear complementarity problem, linear programming or convex quadratic programming can be equivalently reformulated in the form of (1) and thus solved as absolute value equations; see [8,12,17,19]. As far as we know, since Mangasarian and Meyer [14] established existence results for this class of absolute value equations (1), the interest for this subject has increased substantially; see [11,13,20] and reference therein.Several algorithms have been designed to solve the systems of AVEs involving smooth, semismooth and Picard techniques; see [1,7,10,21,22]. In [9], Mangasarian applied the nonsmooth Newton method for solving AVE obtaining global Q-linear convergence and showing its numerical effectiveness.…”
mentioning
confidence: 99%
“…For instance, linear complementarity problem, linear programming or convex quadratic programming can be equivalently reformulated in the form of (1) and thus solved as absolute value equations; see [8,12,17,19]. As far as we know, since Mangasarian and Meyer [14] established existence results for this class of absolute value equations (1), the interest for this subject has increased substantially; see [11,13,20] and reference therein.Several algorithms have been designed to solve the systems of AVEs involving smooth, semismooth and Picard techniques; see [1,7,10,21,22]. In [9], Mangasarian applied the nonsmooth Newton method for solving AVE obtaining global Q-linear convergence and showing its numerical effectiveness.…”
mentioning
confidence: 99%
“…An iterative method based on minimization technique for solving AVEs (1) was proposed in [7]; compared with the linear complementary problem, this method is simple in structure and easy to implement. Iqbal et al [8] showed the Levenberg-Marquardt method which combines the advantages of both steepest descent method and Gauss-Newton method for solving AVEs (1). When the AVEs (1) has multiple solutions, Hossein el at.…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, the implicit fixed-point equation which is equivalent to the LCP(q, M ) is a absolute value equation. Iqbel et al [14] proposed Levenberg-Marquardt method for solving absolute value equations, which is the combination of steepest descent and the Gauss-Newton methods. They proved the global convergence of new method when using the Goldstein line search.…”
Section: Introductionmentioning
confidence: 99%